Fuzzy-Based PID Motion Control for Inhalation-Type Floating Garbage Cleaning Robots - Zheng Li; Xiaoxiao Mi; Michael V. Basin; Hongzheng Zeng (IEEE Access)
This paper introduces an intelligent controlled cleaning tool for picking up underwater floating garbage. An inhalation-type garbage cleaning robot is designed not only to improve the efficiency of garbage collection but also to simplify the controller design. A fuzzy-based PID control strategy is proposed for the position control of the designed cleaning robot. At first, the dynamic model of the robot is built with its parameters estimated by empirical formulas and Fluent software. Then, a fuzzy logic controller is designed to achieve self-adjustment of the PID parameters according to the position error and error change ratio of the robot. On this basis, an incremental PID control technique integrated with the PID parameters given by the fuzzy controller is presented. Furthermore, the cascade PID and fuzzy logic control algorithms for the designed cleaning robot are also developed. Finally, numerical simulations are conducted for comparison with the cascade PID control, the fuzzy logic control, and the proposed fuzzy-based PID control. The simulation results are discussed from different perspectives, showing that the adaptability, robustness, and overall control performance of the robot under the fuzzy-based incremental PID control are better than those of the fuzzy logic control and the cascade PID control.